Unplugged Coding untuk Membaca Permulaan Siswa Kelas I SD: Kajian Studi Pustaka - ZD, Nadhifa Nur Rahmah; Rahmayani, Tria Rohana; Parandrengi, Resyarusyda (Lembaga Yasin AlSys, 2026)
Although beginning reading and unplugged coding have received attention in various educational studies, research that specifically discusses the integration of unplugged coding to improve the beginning reading ability of first-grade elementary school students remains limited. This study aims to examine the potential application of unplugged coding in improving the beginning reading ability of first-grade elementary school students through a conceptual and empirical synthesis of relevant literature. This study uses a qualitative approach with a literature review method, involving 18 scientific articles from accredited national journals and reputable international journals selected based on specific inclusion criteria. Data were collected through a Google Scholar database search using the keywords “unplugged coding,” “membaca permulaan,” “beginning reading,” “computational thinking,” and “sekolah dasar,” and were then analyzed using thematic analysis with coding based on key concepts, namely pattern recognition, algorithms, decomposition, abstraction, debugging, and representation. The results show that the principles of unplugged coding have strong conceptual alignment with beginning reading skills, such as recognizing letters, arranging words, correcting reading errors, and understanding sound symbols. These findings contribute to the development of innovative learning strategies in elementary schools and expand understanding of the integration of 21st-century skills into basic literacy. The conclusion of this study affirms that unplugged coding has the potential to become a holistic approach that develops both basic literacy and computational thinking. The implications of this study include theoretical contributions to the development of literature on unplugged coding and beginning reading, as well as practical implications for teachers, researchers, policymakers, and curriculum developers in designing innovative and adaptive reading instruction. This study also opens opportunities for further research on the experimental effectiveness of unplugged coding on the reading fluency and comprehension of first-grade elementary school students.